Investigation of a Suspect Severe Acute Respiratory Syndrome Coronavirus-2 and Influenza A Mixed Outbreak: Lessons Learned for Long-Term Care Facilities Nationwide. (15th July 2021) - Schrodt, Caroline A; Malenfant, Jason H; Hunter, Jennifer C; Slifka, Kara Jacobs; Campbell, Angela; Stone, Nimalie; Whitehouse, Erin R; Wittry, Beth; Christensen, Bryan; Barnes, John R; Brammer, Lynnette; Hemarajata, Peera; et al.
Abstract: A suspected outbreak of influenza A and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at a long-term care facility in Los Angeles County was, months later, determined to not involve influenza. To prevent inadvertent transmission of infections, facilities should use highly specific influenza diagnostics and follow Centers for Disease Control and Prevention (CDC) guidelines that specifically address infection control challenges.